Compact Fractal Patch Microstrip Antenna Fed by Coplanar Waveguide for Long Term Evolution Communications - Indra Surjati; Yuli Kurnia Ningsih; Syah Alam (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper proposes a new design of compact fractal patch microstrip antenna fed by coplanar waveguide to reduce the antenna dimension and to increase its bandwidth for Long Term Evolution application purposes. The results shown return loss of -23.45 dB and VSWR 1.144 can be achieved by controlling the height and the width of the fractal patch dimension.  Bandwidth of the proposed antenna is 375 MHz which is equal to an increase of 200% compared to the conventional rectangular patch antenna and also the dimension of fractal patch antenna can be reduced until 66%.